STRENGTHENING THE MATHEMATICAL LITERACY THROUGH PROBLEM POSING LEARNING WITH A WORD PROBLEM THEME - Syafrudin, Tomy; Ayu Vitantri, Ciptianingsari (Universitas Muhammadiyah Metro, 2026)
Student mathematical literacy skills is depended teacher or prospective teacher skills to teach mathematical literacy. However, in reality, students' skills as prospective teachers in mathematical literacy are unable to do that. Therefore, a learning method is needed to facilitate the mathematical literacy skills of prospective teacher students. The aim of this research is to depict problem posing learning with a word problem theme that can strengthen the mathematical literacy skills of prospective teacher students. This qualitative research uses descriptive approach which conducted students on third and seventh grade of mathematics education study program for the 2023/2024 academic year. Validation sheet Observation sheets, response questionnaires, assignment sheet, and interview guide sheets are instrument for collecting data in this research. The results of the research show that the steps for learning problem posing with a word problem theme to strengthen students' mathematical literacy are consist of 2 steps. First; (1) choose a point, (2) List attribute to recall prior knowledge, (3) what -if-not-ing- to construct, (4) pose the problem, (5) analyze the problem, (6) communicate (7) emphasized by lecturer. Then second; (1) review, (2) project, (3) emphasized by lecturer. The second step is implemented for meeting after first step. The average validity percentage are 78% of the language content, 84% of mathematics content, and 80% of education content. The practicality of the design learning was 78,69%.